2016
DOI: 10.3892/br.2016.774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of blueberries on migration, invasion, proliferation, the cell cycle and apoptosis in hepatocellular carcinoma cells

Abstract: Abstract. The aim of the present study was to investigate the effects of blueberry consumption on the migration, invasion, proliferation, cell cycle and apoptosis in human hepatocellular carcinoma (HCC) cells, in order to provide clinical treatment and prevention strategies for liver cancer using anticancer therapeutic agents. Rabbiteye blueberry was prepared as fresh juice and fed to rats at low, moderate and high dosages (25, 50 and 100%, respectively) by daily gastric gavage. Seven days later, the rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Accumulating evidence shows the involvement of blueberry or probiotics in the protection of the liver from diseases due to a high-fat diet, 17 liver fibrosis, 18 and hepatocellular carcinoma. 19,20 However, little is known about the effect of the combination of blueberry and probiotics on liver diseases. Our previous study revealed that the combination of blueberry juice and probiotics exhibits a better ameliorating effect on Non-Alcoholic Steatohepatitis (NASH) compared to only blueberry or probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows the involvement of blueberry or probiotics in the protection of the liver from diseases due to a high-fat diet, 17 liver fibrosis, 18 and hepatocellular carcinoma. 19,20 However, little is known about the effect of the combination of blueberry and probiotics on liver diseases. Our previous study revealed that the combination of blueberry juice and probiotics exhibits a better ameliorating effect on Non-Alcoholic Steatohepatitis (NASH) compared to only blueberry or probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated cell cycle-mediated cell transformation and uncontrolled cell growth are some of the fundamental biological features of malignant tumors. Amplification of cyclin genes, especially cyclins D and E, is a crucial event process which occurs in the HCC [ 29 , 30 ]. Masaki et al found that in Long-Evans Cinnamon (LEC) rats, with the progression of HCC, cyclin D1-related kinase activities were dramatically enhanced, in particular, the cyclin D1-related enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the necrotic cells, there was no significant difference in both cells compared to the negative control with a percentage of 4.62% ± 0.16 for Hepa 1c1c7 and 11.14% ± 1.57 for HT-29. Our study corroborates with Zhan et al (2016) who investigated the effects of blueberry juice consumption on rats under human hepatocellular carcinoma (HCC) cells and it was observed that the percentage of apoptosis in the groups receiving blueberry juice dosages was significantly higher compared to the control group. In vitro studies have shown that the effects of blueberry on the protopic effect of anthocyanins in different cancer cell lines have been reported (VUONG et al, 2016;YI et al, 2006).…”
Section: Apoptosis Assaysupporting
confidence: 91%